Reconfigurable flight control based on nonlinear dynamic inversion and dynamic control allocation. (10th March 2014) - Wang, Huidong; Zhang, Xiaoyun; Yi, Jianqiang
Based on nonlinear dynamic inversion (NDI) and dynamic control allocation, a new reconfigurable flight control scheme is proposed for multi effector aircraft. Firstly, basic flight control law is designed by NDI method to produce desired moment command according to the given attitude angle command. Then, the moment command is optimally distributed into individual control surfaces with position and rate constraints by dynamic control allocation (DCA) algorithm. In the face of control surface faults, control reallocation is performed in the remained control surfaces to fulfil flight reconfiguration, and the basic flight control law need not to be redesigned. The reconfigurable flight control scheme is evaluated by a nonlinear six degree–of–freedom (DoF) aircraft model under jammed case and damaged case, respectively. Effectiveness of the reconfigurable flight control method is demonstrated by simulation results.